Study on the Use of Post-Mining Reclaimed Land for the Development of Horticulture-Based Green Infrastructure: A Case Study - Bobby Nugroho Wiwahono; Mussadun Mussadun; Fahrudin Fahrudin (Journal La Lifesci, 2026)
Large-scale mining activities are often not balanced with adequate post-mining management, causing post-mining land to become abandoned and environmental degradation. This study aims to evaluate the potential and opportunities for the implementation of post-mining land reclamation through the development of horticulture-based green infrastructure at PT Radik Jaya Indonesia, Kendal Regency. Identification of land conditions including soil and water characteristics, land cover, and the level of disaster vulnerability is carried out to support sustainable green infrastructure development planning. Research data was obtained through field surveys that included observations, measurements, and interviews, as well as laboratory analysis of soil quality. The collected data was analyzed using the scoring method to determine the level of land suitability in the development of green infrastructure. In addition, SWOT analysis is used to identify internal and external factors that affect the development of green infrastructure at the research site. The results of the study show that the development of horticulture-based green infrastructure has considerable potential as a component to support environmental sustainability as well as improve the community's economy. However, the development still faces a number of challenges, especially related to policy changes and the management of locations that are still actively used for mining activities. The resulting recommendations are expected to be the basis for planning and managing post-mining land reclamation in a sustainable manner, as well as contributing to environmental conservation and improving the economic conditions of the community in the research area.